PENGARUH WORD OF MOUTH DALAM MEMODERASI PERAN KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DITOKO SEPATU DAN SANDAL SAMUDRA SITUBONDO - Khotip, Zainal; Arief, Mohammad Yahya; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Along As time goes by the development of technology is getting faster, so is the footwear industry in Indonesia. footwear industry in Indonesia is also growing rapidly, and consumer demand is increasingly complex over time. are also getting more complex from time to time. The purpose of this research is to analyze the effect of Word of Mouth in moderating the role of Product Quality and Price on Purchasing Decisions in Shoe and Sandal Shops in Indonesia. Product Quality and Price on Purchasing Decisions at Shoe and Sandal Shops Samudra Situbondo. The population in this study were consumers of the Samudra Shoe and Sandal Shop in Situbondo. Sampling technique determined by simple random sampling. Data analysis and hypothesis testing in this study used Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test hypothesis test results using the Smart PLS application 3.0 application, shows that product quality has a significant positive effect on purchasing decisions. Purchasing decisions. Price has a significant positive effect on purchasing decisions purchase decision. Product quality with Word of Mouth moderation of Mouth has a negative and insignificant effect on purchasing decisions. Price with Word of Mouth moderation has a positive but insignificant effect on purchasing decisions.